How Do We Choose Our Giants? Perceptions of Replicability in Psychological Science. Issue 2 (June 2021) - Alister, Manikya; Vickers-Jones, Raine; Sewell, David K.; Ballard, Timothy
Judgments regarding replicability are vital to scientific progress. The metaphor of "standing on the shoulders of giants" encapsulates the notion that progress is made when new discoveries build on previous findings. Yet attempts to build on findings that are not replicable could mean a great deal of time, effort, and money wasted. In light of the recent "crisis of confidence" in psychological science, the ability to accurately judge the replicability of findings may be more important than ever. In this Registered Report, we examine the factors that influence psychological scientists' confidence in the replicability of findings. We recruited corresponding authors of articles published in psychology journals between 2014 and 2018 to complete a brief survey in which they were asked to consider 76 specific study attributes that might bear on the replicability of a finding (e.g., preregistration, sample size, statistical methods). Participants were asked to rate the extent to which information regarding each attribute increased or decreased their confidence in the finding being replicated. We examined the extent to which each research attribute influenced average confidence in replicability. We found evidence for six reasonably distinct underlying factors that influenced these judgments and individual differences in the degree to which people's judgments were influenced by these factors. The conclusions reveal how certain research practices affect other researchers' perceptions of robustness. We hope our findings will help encourage the use of practices that promote replicability and, by extension, the cumulative progress of psychological science.